(A Study on The Use of Tofu By-product To Produce Soymilk) - Indra Neffi Ridwan; Iim Setiadi; Ign -; Suharto - (Warta Industri Hasil Pertanian, 1990)
The research is aimed at studying the effect of stirring time and the ratio of dillution to the extracted protein in the production of soy milk from tofu by-product. The stirring time used were 4,6, and 8 minutes. The dillution ratio of tofu by-product and water were 8:4, *:5, and 8:6. The analysis done include protein content, total solid, total bacteria and organoleptic test. Soy milk obtained from 4 minutes stirring and dillution ratio 8:5 resulted in the highest protein content in total solid i.e. 44.98%. The product is acceptable by the panelists. The total bacteria is 10 col/ml.